A GENEALOGICAL LINGUISTIC IMPLICATION OF THE ABALUHYIA NAMING SYSTEM - Wafula Lwangale, David (IJRDO - Journal of Social Science and Humanities Research, 2017)
Most African communities have a systematic way of naming their children. The naming system of a given community speaks a lot about their way of life. Some communities have family names which cannot be attributed to any meaning. Such names may be regarded generally as clan names. Some names may be attributed to some events and seasons. Others may be inherited in a situation where communities name their children after their dead or living relatives. Therefore, names are not only cultural but also linguistic. The study investigated the naming systems of the Luhyia sub-tribes with a view of establishing the genealogical relatedness of the Luluhyia language dialects. The study established three levels of naming children shared by most of the Luhyia sub-nations. These are based on seasons, events and naming after their dead relatives.